2017
DOI: 10.1080/23273798.2017.1348528
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing cause from effect – many deficits associated with developmental dyslexia may be a consequence of reduced and suboptimal reading experience

Abstract: (2018) Distinguishing cause from effect -many deficits associated with developmental dyslexia may be a consequence of reduced and suboptimal reading experience, Language, Cognition and Neuroscience, 33:3, 333-350, DOI: 10.1080/23273798.2017 The cause of developmental dyslexia is still unknown despite decades of intense research. Many causal explanations have been proposed, based on the range of impairments displayed by affected individuals. Here we draw attention to the fact that many of these impairments ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 199 publications
(203 reference statements)
1
72
1
1
Order By: Relevance
“…Peterson et al, ) and may cause researchers to revisit the causal role of RAN in developmental dyslexia (cf. Huettig et al, ). Relatedly, these results can be relevant for neuropsychological/psychoeducational assessment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peterson et al, ) and may cause researchers to revisit the causal role of RAN in developmental dyslexia (cf. Huettig et al, ). Relatedly, these results can be relevant for neuropsychological/psychoeducational assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas, some developmental studies reported a unidirectional effect of (early) RAN on later reading skills (Lervåg & Hulme, ; Verhagen, Aarnoutse, & van Leeuwe, ; Wei, Georgiou, & Deng, ), others found a reciprocal relation between RAN and reading (Compton, ; Peterson et al, ; Wolff, ), and hence, reading experience is not only influenced by but is also a causal influence on RAN (cf. Huettig, Lachmann, Reis, & Petersson, ). Indeed, in a recent longitudinal study from prekindergarten to fourth‐grade, Peterson et al () did find evidence for a causal effect of early reading skills on children's RAN but only at the very beginning of literacy acquisition (while the relation was reversed in older children).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a related literature on factors correlating with dyslexia (e.g.,Huettig, Lachmann, Reis, & Petersson, 2018), which is not covered here unless it can be assumed that the variables also correlate with individual differences in normal reading rate.…”
mentioning
confidence: 99%
“…Huettig, Lachmann, Reis, and Petersson (2018) suggest that many deficits associated with developmental dyslexia are in fact a consequence of reduced and/or suboptimal reading experience. They point out that almost all deficits observed in individuals with dyslexia have also been observed in illiterate and low literate people.…”
mentioning
confidence: 99%